Typology of plazas adjacent to tall buildings: a case study of Kuala Lumpur City - Ibrahim, Md. Najib; Abdul Majid, Noor Hanita (1999)
This paper presents a result of a field research on Plazas Adjacent to Tall Buildings (PATB) in CBD Kuala Lumpur City. The result shows that only eight PATB are built in the city. The PATB are organised in three distinct typologies. This paper also discusses on the thermal effects at the plazas and its utilization.